Analisa Kondisi Minyak Trafo Berdasarkan Hasil Uji Dissolved Gas Analisys Pada Trafo Daya #1 Di PT.PLN (PERSERO) GARDU INDUK KOTABUMI - Afrida, Yenni; Fitriono (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2022)
Abstract Transformer oil is very important because it functions as a coolant and also as an insulator. In transformer oil there are dissolved gases that can cause failure of the transformer due to gas failure (fault gas). This research was conducted to determine the condition of transformer oil by analyzing the results of the Dissolved Gas Analysis (DGA) test. The DGA (Dissolved Gas Analysis) test is used to determine the type of failure in a transformer that has been operating for years. The DGA test is carried out by monitoring fault gases such as H2, CH4, CO, CO2, C2H4, C2H6, C2H2, O2, N2 and O2N2 which generally cannot be detected in testing the characteristics of transformer oil. Based on the test results using the Total Dissolve Gas Analysis (TDCG) method condition 1 with the amount of flammable gas 202.845 ppm with the interpretation that the transformer can operate normally. The test results using the Roger's Ratio method on the Power Transformer 1 GI Kotabumi obtained codes 0 0 0. From the combination of the 3 codes above, it shows that the transformer oil is in good condition. The results of the test using the Key Gas method on Power Transformer 1 GI Kotabumi obtained a CO value of 56 percent caused by overheating of cellulose or overheating of solid insulation in the transformer but that value is still far from the threshold Keywords Dissolved Gas Analysis (DGA),Transformer oil, Roger'r ratio method, KeyGas